2020
DOI: 10.2147/cmar.s246103
|View full text |Cite
|
Sign up to set email alerts
|

<p>A Sensitive and Simplified Classifier of Cervical Lesions Based on a Methylation-Specific PCR Assay: A Chinese Cohort Study</p>

Abstract: These authors contributed equally to this workObjective: The aim of this study is to assess the diagnostic and screening performance of a standardized methylation-specific real-time PCR assay targeting SOX1 and PAX1 genes for cervical cancer in a Chinese cohort. Methods: Genomic DNA was extracted from cervical exfoliated cells and converted by sodium bisulfite and then analyzed by qMSP assay. Ct values were collected for PAX1 and SOX1 as target genes and β-actin as an endogenous reference gene. The samples inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…In the ASCUS group, nine cases were identified as methylation-positive for CIN2+, with no methylationnegative CIN2+ cases. Overall, 37 cases were methylation-positive, resulting in a colposcopy referral rate of 22.29% (37 out of 166) 16. The current study confirmed these trends, with methylation positivity rates increasing with lesion severity: 17.1% in control group, 22.5% in CIN1 group, 100% in CIN2 group, 90% in CIN3 group, and 100% in CC group.…”
supporting
confidence: 82%
See 2 more Smart Citations
“…In the ASCUS group, nine cases were identified as methylation-positive for CIN2+, with no methylationnegative CIN2+ cases. Overall, 37 cases were methylation-positive, resulting in a colposcopy referral rate of 22.29% (37 out of 166) 16. The current study confirmed these trends, with methylation positivity rates increasing with lesion severity: 17.1% in control group, 22.5% in CIN1 group, 100% in CIN2 group, 90% in CIN3 group, and 100% in CC group.…”
supporting
confidence: 82%
“…Our prior research on PAX1/SOX1 gene methylation in cervical cells from 487 patients showed that methylation rates was 100% in cancer group, 11.5% in cervical inflammation group, 45.1% in LSIL group, and 68.5% in HSIL group 16 . The current study confirmed these trends, with methylation positivity rates increasing with lesion severity: 17.1% in control group, 22.5% in CIN1 group, 100% in CIN2 group, 90% in CIN3 group, and 100% in CC group.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The methylation index, evaluated with MSP, has been the most frequently used method to assess the methylation level. There are several methods for calculating methylation levels, including MI = ΔCt [ 50 ], MI = 2 −ΔCt [ 51 ], MI = 10,000 × 2 ΔCt where ΔCt = Ct target gene - Ct internal reference [ 52 ], MI = 2 −ΔΔCt where ΔΔCt = ΔCt sample - ΔCt calibrator [ 51 ], MI = Ct target gene /Ct internal reference [ 52 ], and MI = Ct [ 26 , 41 , 53 ]. Regarding the use of Ct as an MI index, the lower the Ct value is, the higher the methylation level is, and the endogenous reference such as ACTB used in this study should be valid, indicating that the sample treatment was effective.…”
Section: Discussionmentioning
confidence: 99%
“…20 Ezigbo et al 256 included the VWF:CB to help characterize VWD in the Nigerian population. Zhang et al 257 included the VWF:CB in their study of VWF level and activity in healthy Chinese. Heilmann et al 258 included the VWF:CB in their study of AVWS in 74 patients on long-term support with the VAD HeartMate II.…”
Section: The Next Decade-the 2010smentioning
confidence: 99%